LQG-based optimal control approach of an electronic throttle valves using DC servo system - Phan, Van Du; Dinh, Van Nam; Nguyen, Phuc Ngoc; Duong, Dinh Tu; Ta, Hung Cuong; Le, Dinh Cong; Pham, Ho Vinh; Nguyen, Huu Thang (Institute of Advanced Engineering and Science, 2025)
A direct current (DC) motor is used for automotive electronic throttle valves (AETV) to adjust incoming air into the engine’s combustion system, which has many advantages such as smooth, fast response, and simplicity. However, high-accuracy tracking control for AETV faces various obstacles because of the nonlinear features, hard identification, and noise. In this paper, a model of the AETV with four states in the form of a state space is developed. Then, a Kalman filter is formulated to eliminate the impact of measurement noise. The Kalman filter gain is obtained via the solve the linear quadratic gaussian (LQG) equation. Next, the optimal control based linear quadratic regulation (LQR) and Kalman filter are presented in which the control gain is constructed by the Riccati equation with the assistance of MATLAB/Simulink software. Finally, simulation studies are conducted to demonstrate the efficiency of the suggested method for the AETV system with other control strategies.